European drug report / 2018 (European drug report trends and developments, 2018)
The Trends and Developments report presents a toplevel overview of the drug phenomenon in Europe, covering drug supply, use and public health problems as well as drug policy and responses. Together with the online Statistical Bulletin and 30 Country Drug Reports, it makes up the 2018 European Drug Report package. This report is based on information provided to the EMCDDA by the EU Member States, the candidate country Turkey and Norway in an annual reporting process. The purpose of the current report is to prove an overview and summary of the European drug situation and responses to it. The statistical data reported here relate to 2016 (or the last year available). Analysis of trends is based only on those countries providing sufficient data to describe changes over the period specified. The reader should also be aware that monitoring patterns and trends in a hidden and stigmatised behaviour like drug use is both practically and methodologically challenging. For this reason, multiple sources of data are used for the purposes of analysis in this report. Although considerable improvements can be noted, both nationally and in respect to what is possible to achieve in a European level analysis, the methodological difficulties in this area must be acknowledged. Caution is therefore required in interpretation, in particular when countries are compared on any single measure. Caveats and qualifications relating to the data are to be found in the online version of this report and in the Statistical Bulletin, where detailed information on methodology, qualifications on analysis and comments on the limitations in the information set available can be found. Information is also available there on the methods and data used for European level estimates, where interpolation may be used.